Molecularly targeted therapies in metastatic pancreatic cancer: A systematic review - Zagouri, F.; Sergentanis, T.N.; Chrysikos, D.; Zografos, C.G.; Papadimitriou, C.A.; Dimopoulos, M.-A.; Filipits, M.; Bartsch, R. (Pancreas, 2013)
Pancreatic cancer is the fourth leading cause of cancer-related death. Most patients present with an advanced stage of disease that has a dismal outcome, with a median survival of approximately 6 months. Evidently, there is a clear need for the development of new agents with novel mechanisms of action in this disease. A number of biological agents modulating different signal transduction pathways are currently in clinical development, inhibiting angiogenesis and targeting epidermal growth factor receptor, cell cycle, matrix metalloproteinases, cyclooxygenase-2, mammalian target of rapamycin, or proteasome. This is the first systematic review of the literature to synthesize all available data coming from trials and evaluate the efficacy and safety of molecular targeted drugs in unresectable and metastatic pancreatic cancer. However, it should be stressed that although multiple agents have been tested, only 9 phase 3 trials have been conducted and one agent (erlotinib) has been approved by the Food and Drug Administration for use in clinical practice. As knowledge accumulates on the molecular mechanisms underlying carcinogenesis in the pancreas, the anticipated development and assessment of molecularly targeted agents may offer a promising perspective for a disease which, to date, remains incurable. Copyright © 2013 by Lippincott Williams & Wilkins.
Keywords: Molecularly targeted agents; Pancreatic cancer; systematic review; Target therapy